2017
DOI: 10.1155/2017/1765428
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the Bering Sea and East Asia Rules in Long-Range Forecasting

Abstract: the utility of the Bering Sea Rule (BSR) and the East Asia Rule (EAR) for making forecasts in the two-to-four-week time frame for the central USA region is examined. It is demonstrated using autocorrelation and Fourier transforms that there may be a degree of predictability in this time frame using the PNA, another teleconnection index, or some variation of them. Neither the BSR nor EAR based forecasts showed skill over climatology in the traditional sense, but using signal detection techniques these indexes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…Such occurrences were comparatively rare during El Nino or Neutral years; however, some of these years were associated with multiple occurrences. Many researchers showed that the Pacific Ocean Basin was more active in terms of blocking activity [24] and references therein during La Nina years, and this is associated with a more active storm track (e.g., [16,17]). Thus, the greater number of blocking events associated with heavy rain in the central USA is consistent with the idea that there are more opportunities for simultaneous occurrence of each.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such occurrences were comparatively rare during El Nino or Neutral years; however, some of these years were associated with multiple occurrences. Many researchers showed that the Pacific Ocean Basin was more active in terms of blocking activity [24] and references therein during La Nina years, and this is associated with a more active storm track (e.g., [16,17]). Thus, the greater number of blocking events associated with heavy rain in the central USA is consistent with the idea that there are more opportunities for simultaneous occurrence of each.…”
Section: Discussionmentioning
confidence: 99%
“…They impose a low-frequency planetary-scale wave with a period of about two to three weeks on a zonal flow as well as a synopticscale perturbation of about three days in length to describe the transitions between the positive and negative phases of the NAO and the presence and role of blocking in these transitions. The model was extended by [16] to demonstrate the interactions among the mean flow, planetary waves, and synoptic eddies and proposed a new mechanism to explain the onset or destruction of blocking regimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This peak is evident in the autocorrelation of the IE figures as well. While this time period is beyond the scope of our work here, predictability in the 20-30 day period was discussed in a recent study [55]. That study found statistically significant peaks in this time frame, using the FFT and autocorrelation analysis applied to a 67-year time series of the Pacific North America Index [55].…”
Section: Discussionmentioning
confidence: 93%
“…While this time period is beyond the scope of our work here, predictability in the 20-30 day period was discussed in a recent study [55]. That study found statistically significant peaks in this time frame, using the FFT and autocorrelation analysis applied to a 67-year time series of the Pacific North America Index [55]. They attributed these to persistent and quasi-stationary Rossby wave trains occurring within the Pacific Ocean basin, and this information can be used to make weather predictions in the 2-4 week time period.…”
Section: Discussionmentioning
confidence: 99%